Electronic document tracking system: a prototype - Demong, Rochin; Abu Hassan, Lailatul Faizah; Tuan Besar, Tuan Badrol Hisham; Zulkifli, Zulhaimi (2008)
With rapidly-changing technology and increasing emphasis in managing information properly, Electronic Document Tracking System (EDTS) has been developed as a solution system to improve the efficiency of retrieving the document online at anytime and tracking the movement of documents in and out of Faculty of Office Management and Technology (FOMT). Documents are central to the functioning of an organization. Among other roles, they are critically important as a means of communication, as organizational memory, and in business processes. In addition, office workers spend as much as 60 percent of their time handling documents. For these reasons, FOMT have tried to improve document handling and use through the application of information technology. EDTS is an application developed to provide assistance in electronic document processing and tracking for users. It was developed within windows environment using Open Source tools such as PHP and MySQL. The application relies on TCP/IP and internet to support server and client communications. The main benefit of the prototype system is the user can view the document at anytime and from anywhere. This system is enabling to save time and cost. The purposes of this study is to show the value of new technology for managing documents, to illustrate the variety of ways this value can be realized, to develop some structure for understanding this rapidly evolving field, and to suggest some actions the administrators can take now to prepare for this revolution in information management.